2023
DOI: 10.1002/cb.2211
|View full text |Cite
|
Sign up to set email alerts
|

Believing in change: The role of implicit theory on consumer's perception of the brand's corporate social responsibility message

Abstract: With the sustainable consumption paradigms, corporate social responsibilities (CSR) across industries have been under scrutiny. However, little research exists on how brand's business model and consumers' characteristics are intertwined to influence CSR evaluation. Our study aims to examine how the brand type (e.g., fast vs. slow business model) influences the relationships among CSR‐brand fit, authenticity, and skepticism, thus improving attitudes toward the brand. In addition, based on the implicit theory, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…It suggests that fixed-mindset customers with high brand trust are more likely to exhibit positive cognitive and affective responses toward a brand. For customers with a fixed mindset, established brand trust acts as a reinforcing factor, improving their level of engagement owing to its alignment with their preexisting views (Kim and Kim, 2023). Contrastingly, customers with a growth mindset may require additional cognitive and emotional stimuli to augment their level of engagement, even if they already exhibit high trust in the brand (Jain et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It suggests that fixed-mindset customers with high brand trust are more likely to exhibit positive cognitive and affective responses toward a brand. For customers with a fixed mindset, established brand trust acts as a reinforcing factor, improving their level of engagement owing to its alignment with their preexisting views (Kim and Kim, 2023). Contrastingly, customers with a growth mindset may require additional cognitive and emotional stimuli to augment their level of engagement, even if they already exhibit high trust in the brand (Jain et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Those with growth mindsets are likely to accept brand extensions and are more likely to use the services again in case of service failure, based on the assurance of better service being provided next time (Stough and Carter, 2023). Other studies revealed that a growth mindset notably affects customers’ consumption behaviors and drives them to buy sustainable food (Kim and Kim, 2023; Rahnama and Popkowski Leszczyc, 2022). More research on the influence of mindsets on consumer behavior is needed (Japutra and Song, 2020; Mitrega et al , 2022).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation